Pembuatan Ergonomic Mechanical Keyboard untuk Mengurangi Cidera Tangan Menggunakan Teknologi Arduino - Muhammad Akbar Maulana (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
In our daily lives, computers and keyboards are essential tools for both work and gaming. However, despite the variety of keyboards available on the market, few consider the comfort and needs of individual users. To solve this issue, a mechanical keyboard that can be adjusted in width, shape, and positioning is required to lessen hand injuries when used for extended periods. This research produces a mechanical keyboard hardware prototype using Arduino as the main component. The device will be connected to an electronic circuit and use C Language as supporting software. Tests were conducted to compare existing keyboards on the market related to function tests, compatibility, usability, and performance tests. The results show that all hardware components function perfectly at 98% capacity.